Towards optimizing caesarean section: a five-year review of caesarean sections at a Southern Nigeria hospital - Osegi, Nkencho; Makinde, Olakunle I. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Monitoring caesarean sections at hospital level is essential to reduce unnecessary caesarean sections while still ensuring adequate access to caesarean section. This study was conducted to determine the caesarean section rate and indications for caesarean section at the study centre and provide objective data for institutional interventions towards reducing unnecessary caesarean sections in the centre. Methods: A retrospective descriptive study of patients that had caesarean sections between 1st January 2013 and 31st December 2017 at the Federal Medical Centre, Yenagoa, Nigeria. Data were analyzed using Statistical Package for Social Sciences version 22. Results: There were 5,793 deliveries and 1,654 were by caesarean section. The average caesarean section rate was 28.6%. The leading indications for caesarean section were cephalopelvic disproportion (26.6%), previous cesarean section (18.2%), suspected fetal distress (11.2%), severe preeclampsia/eclampsia (7.9%), obstructed labour (6%), and breech presentation (5.9%). Conclusions: The 28.6% caesarean section rate in this study falls within a widely varied rate across Nigeria at hospital level but is comparable to rates within the south-south geopolitical zone of Nigeria. The leading indications for caesarean section are modifiable, thus there is room for institutional intervention to reduce unnecessary caesarean sections. Collaborative research between institutions is required to assess peculiar regional determinants of caesarean section towards developing suitable interventions to reduce unnecessary caesarean sections regionally.